2018
DOI: 10.1016/j.ijid.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Ebola vaccine development: Systematic review of pre-clinical and clinical studies, and meta-analysis of determinants of antibody response variability after vaccination

Abstract: Various platforms have been evaluated in humans, including Ad26, Ad5, ChimpAd3, DNA, MVA, and VSV. In addition to platforms, viral strain used for antibody detection influences antibody response. However, variability remained mostly unexplained. Therefore, comparison of vaccine immunogenicity needs randomised controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…A first meta-analysis has now been published by Gross and colleagues summarizing antibody responses of all clinical trials in which VSV-EBOV was tested. 68 All studies observed induction of EBOV GP-specific antibody responses following immunization with VSV. Antibody responses developed at 14 days p.v., peaked around day 28 and remained detectable for at least 2 years.…”
Section: Correlates Of Protection and Duration Of Immune Responsesmentioning
confidence: 99%
“…A first meta-analysis has now been published by Gross and colleagues summarizing antibody responses of all clinical trials in which VSV-EBOV was tested. 68 All studies observed induction of EBOV GP-specific antibody responses following immunization with VSV. Antibody responses developed at 14 days p.v., peaked around day 28 and remained detectable for at least 2 years.…”
Section: Correlates Of Protection and Duration Of Immune Responsesmentioning
confidence: 99%
“…To do this, we can start by doing a simple search in PubMed or Google Scholar with search terms Ebola AND vaccine. While doing this step, we identify a systematic review and meta-analysis of determinant factors influencing antibody response from vaccination of Ebola vaccine in non-human primate and human [7], which is a relevant paper to read to get a deeper insight and identify gaps for better formulation of our research question or purpose. We can still conduct systematic review and meta-analysis of Ebola vaccine because we evaluate safety as a different outcome and different population (only human).…”
Section: Preliminary Research and Idea Validationmentioning
confidence: 99%
“…EBOV-specific humoral immune responses are likely necessary for protection from severe disease and most studies measure antibodies that bind the EBOV glycoprotein (GP) as the primary marker for immunogenicity ( 13 ) and as surrogate for vaccine efficacy according to the animal rule ( 14 ), a process by which animal study can replace human efficacy trials when they are not feasible or ethical. A follow up study of the 100% efficacious rVSV-EBOV found that the majority of vaccinated subjects maintained EBOV specific antibodies two years after vaccination ( 15 ).…”
Section: Introductionmentioning
confidence: 99%